A nonlinear panel model of cross-sectional dependence - George Kapetanios; James Mitchell; Yongcheol Shin (Queen Mary University of London, School of Economics and Finance, 2010)
This paper proposes a new panel model of cross-sectional dependence. The model has a number of potential structural interpretations that relate to economic phenomena such as herding in financial markets. On an econometric level it provides a flexible approach to the modelling of interactions across panel units and can generate endogenous cross-sectional dependence that can resemble such dependence arising in a variety of existing models such as factor or spatial models. We discuss the theoretical properties of the model and ways in which inference can be carried out. We supplement this analysis with a detailed Monte Carlo study and two empirical illustrations.
Keywords: C31; C32; C33; G14; 330; cross-sectional dependence; nonlinearity; factor models; panel models; fixed effects; Finanzmarkt; Herdenverhalten; Nichtlineares Verfahren; Querschnittsanalyse; Panel